Aplikasi pengendalian hayati untuk penyakit parasitik pada Kerbau Rawa di Desa Tanjung Pering Kecamatan Inderalaya Kabupaten Ogan Ilir - Afnur Imsya; Yuanita Windusari; Laila Hanum; Hikayati Hikayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
One of the problems that occur in buffalo farms in tanjung pering village is that buffaloes often experience health problems caused by parasites. The results of initial observations showed that livestock showed symptoms such as dry skin, hair loss, loss of appetite, lethargy and finally decreased productivity and even death. This disease often appears during the transition from the rainy season to the dry season. Based on the results of research that has been carried out on faecal samples of swamp buffalo in the villages of tanjung pering and tanjung senai, the identification of the presence of parasite eggs of cestode, nematode and trematode. This activity aims to provide knowledge innovation to the farming community in tanjung pering village about the methods and importance of biological control as an alternative to controlling the spread of parasitic diseases. The methods used in this activity are counseling, training in the form of demonstrations and activity evaluations. The results of the extension activities show that there is an increase in the understanding of farmers about the causes and symptoms of the disease, how to handle and biological control of parasites by using the nematophagus fungus. The conclusion of this activity is the existence of continuous application of disease control using biological agents to suppress livestock populations experiencing parasitic infections.